1988
DOI: 10.3758/bf03337686
|View full text |Cite
|
Sign up to set email alerts
|

Contextual modulation of simultaneous associations

Abstract: Subjects. Twenty-four male and 24 female adult Sprague-Dawley descended naive rats served as subjects. Body weights were 240-395 g for males and 195-280 g for females. The animals were singly housed in a vivarium maintained on a 16:8-h light:dark cycle, with experimental manipulations occurring near the middle of the light phase. The 1988, 26 (4), [371][372][373][374] Bulletin of the Psychonomic Society Contextual modulation of simultaneous associations LOUIS D. MATZEL, JUAN CASTILLO, and RALPH R. MILLER Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…Although photokinesis was significantly reduced in Group F(2) compared with Group UP(2), which received the CS and UCS unpaired, it is somewhat surprising that Group F(2) did not differ from animals trained with the simultaneous CS–UCS arrangement, Group S(2). This stimulus arrangement is commonly used in vertebrate preparations and typically produces stronger conditioned responding than does simultaneous conditioning (e.g., Matzel, Castillo, & Miller, 1988; Matzel, Held, & Miller, 1988). It seems likely that the more contiguous occurrence of the CS and UCS in the forward condition, in which the CS overlapped the UCS, enhanced either the strength of the association or the expression of the conditioned response and that Hermissenda is more likely to benefit from this arrangement than are higher organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although photokinesis was significantly reduced in Group F(2) compared with Group UP(2), which received the CS and UCS unpaired, it is somewhat surprising that Group F(2) did not differ from animals trained with the simultaneous CS–UCS arrangement, Group S(2). This stimulus arrangement is commonly used in vertebrate preparations and typically produces stronger conditioned responding than does simultaneous conditioning (e.g., Matzel, Castillo, & Miller, 1988; Matzel, Held, & Miller, 1988). It seems likely that the more contiguous occurrence of the CS and UCS in the forward condition, in which the CS overlapped the UCS, enhanced either the strength of the association or the expression of the conditioned response and that Hermissenda is more likely to benefit from this arrangement than are higher organisms.…”
Section: Resultsmentioning
confidence: 99%
“…This reliance on long stimulus durations may have contributed to one curious dissimilarity between associative processes in Hermissenda and vertebrates. Grover and Farley (1987) presented data that suggested that simultaneous pairings of a CS and UCS resulted in stronger conditioned responding in Hermissenda than did forward CS-UCS pairings, a somewhat anomalous result in the conditioning literature (e.g., Burkhardt & Ayres, 1978;Heth, 1976;Matzel, Castillo, & Miller, 1988;Schneiderman & Gormezano, 1964). However, Grover and Farley compared the simultaneous presentation of a 30-s light CS with 30 s of rotation to the analogous forward presentation of those stimuli; that is, the onset of the CS preceded the onset of the UCS by 30 s. Unfortunately, the temporal parameters of the interstimulus-interval (ISI) function for this particular conditioning preparation have not yet been determined, and in many preparations, a 30-s forward ISI is outside the range that will support conditioning.…”
mentioning
confidence: 99%
“…Sin embargo, en otros estudios el cambio de contexto posterior a una discriminación sucesiva, ha producido la reaparición de la respuesta entrenada durante la primera discriminación con la disminución de la respuesta aprendida durante la segunda discriminación (Vila, Romero, & Rosas, 2002). Mientras que un cambio de contexto después de la adquisición de una discriminación con un ED compuesto por dos elementos presentados de manera simultánea produce un decremento de la respuesta sólo para el componente del ED que produce una menor respuesta por separado (Matzel, Castillo, & Miller, 1988). Estos estudios sugieren que el cambio de contexto, provocará la reaparición de la respuesta de discriminación adquirida con menor fuerza, más que un decremento por generalización.…”
Section: Introductionunclassified